(untitled) (The Pakistan Development Review, 2008)
Labour market performance in Pakistan has improved markedly in recent years. This paper examines the extent to which young people have benefited from this improvement, using the labour market vulnerability framework that was recently introduced by the ILO. This framework can be used to assess the difficulties young people face on the road to decent employment, and may also serve as a basis for the development of appropriate policies and interventions. Drawing on empirical evidence from various surveys, in particular the Labour Force Survey, we conclude that vulnerability among the youth has generally been reduced since 1999-2000. Vulnerability of women has been reduced through higher enrolment rates in education, and unemployment among both men and women has declined. Far less progress has been made in reducing vulnerability among the employed, and youth still face numerous obstacles that hamper the attainment of decent employment. The paper offers recommendations on the role of labour market information in reducing youth vulnerability. JEL classification: J40, J13 Keyword: Labour Market; Youth; Pakistan